Flagellin C decreases the expression of the Gossypium hirsutum cation/proton exchanger 3 gene to promote calcium ion, hydrogen peroxide, and nitric oxide and synergistically regulate the resistance of cotton to Verticillium wilt - Zhou, Heng; Wang, Yi; Zhang, Yihao; Xie, Yijing; Nadeem, Hasan; Tang, Canming (Frontiers in Plant Science, 2022)
To date, no ideal effective method for controlling Verticillium wilt in upland cotton (Gossypium hirsutum) has been defined. The purpose of this study was to determine the effects and mechanism through which flagellin C (FLiC) regulates the Gossypium hirsutum cation/proton exchanger 3 gene (GhCAX3), induces plant immunity, and increases resistance to Verticillium wilt. The FLiC gene was cloned from an endophytic bacterium (Pseudomonas) isolated from roots of the upland cotton cultivar Zhongmiansuo 41. The biocontrol effects of FLiC purified in vitro on resistant and susceptible upland cotton cultivars were 47.50% and 32.42%, respectively. FLiC induced a hypersensitive response (HR) in leaves of tobacco and immune responses in upland cotton. Transcriptome data showed that treatment with FLiC significantly enriched the calcium antiporter activity-associated disease-resistant metabolic pathway in seedlings. Moreover, FLiC downregulated GhCAX3 expression to accelerate intracellular calcium ion (Ca2+) influx and stimulate increases in the intracellular hydrogen peroxide (H2O2) and nitric oxide (NO) contents. The coordinated regulation of Ca2+, H2O2 and NO enhanced cotton resistance to Verticillium wilt. Furthermore, transgenic Arabidopsis plants overexpressing FLiC showed significantly improved resistance to Verticillium wilt. FLiC may be used as a resistance gene and a regulator to improve resistance to Verticillium dahliae (VD) in upland cotton.